Use of POCUS (Point of Care Ultrasound) in skin and soft tissue infections (Research, Society and Development, 2023)
The objective was to evaluate the applicability of the use of point of care ultrasound (POCUS) in the care of patients with soft tissue abscess in order to optimize the prognosis and help in the treatment of the patient. This is an integrative literature review, with a qualitative descriptive character, elaborated through the collection of data from primary sources. Retrospective observational studies, systematic literature reviews, prospective descriptive studies, case-control studies and meta-analyses were included. It was concluded that the use of point-of-care ultrasound (POCUS) in clinical practice is paramount as a diagnostic support for urgent and emergency polytrauma patients, as well as routine users who seek prompt care at health centers, as is the case with patients with soft tissue abscesses. It is essential, however, to establish and register training and improvement programs, with different levels of training and quality criteria to guarantee the safety and effectiveness of the use of POCUS in the extra and intra-hospital environment. There is a need for further studies on the subject because it is a technological resource for propaedeutics in several specialties and the existence of limited research on the use of the tool in the initial care of patients.